background image

2. down

a

=

Q

i

dom

a

down

a

i

.

Proof.

We will prove only the first as the second is dual.

up

a

=

{

c

Q

Z

|

c

a

}

=

{

c

Q

Z

| ∀

i

dom

a

:

c

i

a

i

}

=

{

c

Q

Z

| ∀

i

dom

a

:

c

i

up

a

i

}

=

Q

i

dom

a

up

a

i

.

Proposition 31.

If every

(

A

i

;

Z

i

)

is a filtered complete lattice filtrator, then

(

Q

A

;

Q

Z

)

is a

filtered complete lattice filtrator.

Proof.

That

Q

A

is a complete lattice is already proved above. We have for every

a

Q

A

d

Q

A

up

a

=

λi

dom

A

:

d

{

x

i

|

x

up

a

}

=

λi

dom

A

:

d

{

x

|

x

up

a

i

}

=

λi

dom

A

:

d

up

a

i

=

λi

dom

A

:

a

i

=

a

.

Obvious 32.

If every

(

A

i

;

Z

i

)

is a prefiltered complete lattice filtrator, then

(

Q

A

;

Q

Z

)

is a

prefiltered complete lattice filtrator.

Proposition 33.

Let

A

i

is a non-empty poset. Every

(

A

i

;

Z

i

)

is a semifiltered complete lattice

filtrator iff

(

Q

A

;

Q

Z

)

is a semifiltered complete lattice filtrator.

Proof.

up

a

up

b

λi

dom

A

:

up

a

i

up

b

i

λi

dom

A

:

a

i

b

i

a

b

for every

a, b

Q

A

(used the fact that up

a

i

0

because up is injective).

Proposition 34.

Let

(

A

i

;

Z

i

)

are filtrators and each

Z

i

is a complete lattice. For

a

Q

A

:

1. Cor

a

=

λi

dom

a

:

Cor

a

i

;

2. Cor

a

=

λi

dom

a

:

Cor

a

i

.

Proof.

We will prove only the first, because the second is dual.

Cor

a

=

d

Q

Z

up

a

=

λi

dom

a

:

d

Z

i

{

x

i

|

x

up

a

}

=

λi

dom

a

:

d

Z

i

{

x

|

x

up

a

i

}

=

λi

dom

a

:

d

Z

i

up

a

i

=

λi

dom

a

:

Cor

a

i

.

Proposition 35.

If each

(

A

i

;

Z

i

)

is a filtrator with (co-)separable core, then

(

Q

A

;

Q

Z

)

is a

filtrator with (co-)separable core.

Proof.

We will prove only for separable core, as co-separable core is dual.

x

Q

A

y

⇔ ∀

i

dom

A

:

x

i

A

i

y

i

⇒ ∀

i

dom

A

X

up

x

i

:

X

A

i

y

i

⇔ ∃

X

up

x

i

dom

A

:

X

i

A

i

y

i

⇔ ∃

X

up

x

:

X

Q

A

y

for every

x, y

Q

A

.

Obvious 36.

1. If each

(

A

i

;

Z

i

)

is a down-aligned filtrator, then

(

Q

A

;

Q

Z

)

is a down-aligned filtrator.

2. If each

(

A

i

;

Z

i

)

is an up-aligned filtrator, then

(

Q

A

;

Q

Z

)

is an up-aligned filtrator.

Proposition 37.

If every

b

i

is substractive from

a

i

where

a

and

b

are

n

-indexed families of

distributive lattices with least elements (where

n

is an index set), then

a

\

b

=

λi

n

:

a

i

\

b

i

.

Proof.

We need to prove

(

λi

n

:

a

i

\

b

i

)

b

= 0

and

a

b

=

b

(

λi

n

:

a

i

\

b

i

)

.

Really,

(

λi

n

:

a

i

\

b

i

)

b

=

λi

n

: (

a

i

\

b

i

)

b

i

= 0

and

b

(

λi

n

:

a

i

\

b

i

) =

λi

n

:

b

i

(

a

i

\

b

i

) =

λi

n

:

b

i

a

i

=

a

b

.

Proposition 38.

If every

A

i

is a distributive lattice, then

a

\

b

=

λi

dom

A

:

a

i

\

b

i

for every

a,

b

Q

A

whenever every

a

i

\

b

i

is defined.

Proof.

We need to prove that

λi

dom

A

:

a

i

\

b

i

=

d

{

z

Q

A

|

a

b

z

}

.

To prove it is enough to show

a

i

\

b

i

=

d

{

z

i

|

z

Q

A

, a

b

z

}

that is

a

i

\

b

i

=

d

{

z

A

i

|

a

i

b

i

z

}

what is true by definition.

Proposition 39.

If every

A

i

is a distributive lattice with least element, then

a

#

b

=

λi

dom

A

:

a

i

#

b

i

for every

a, b

Q

A

whenever every

a

i

#

b

i

is defined.

Function spaces of posets

5